KETUNTASAN PENDEKATAN PEMBELAJARAN KONSTEKTUALDALAM MENGEMBANGKAN KEMAMPUAN MENULIS NASKAH PIDATO - Susanto, Andik (WAHANA PEDAGOGIKA, 2016)
The purpose of thisstudywasto. (1) To determine thecompleteness of studentafter contextual learning in developing the ability to write speeches. This research data is of events and information about the practice of contextual learning approach. Data collection techniques used include observation techniques and test engineering. There sult of this study indicate that in writing speeches grade 9 students learning SMP M 1 Sumber rejo years 2014/2015 that mastery learning refers to the process of assessment base don there sult of this study conclude that after learning mastery is achieved with a value above the KKM.